Dalszy ciąg reform o uszlachetnienie panegiryków (portret Emilii Plater w twórczości enkomiastycznej) - Patro-Kucab, Magdalena (Słowo. Studia językoznawcze, 2014)
The author discusses in the article Polish pieces (Konstanty Gaszyński’s - Wiersz z okoliczności wejścia w szeregi walczących panien Emilii Platerówny i Marii Raszanowiczówny and Antoni Edward Odyniec’s - Smug kowieński. Zdarzenie prawdziwe), as well as German lyrics: Moritz Veit’s – Vor dem Zelte der Gräfin Plater, Ernst Ortlepp’s – Gräfin Plater and anonymous author’s – Die Gräfin Plater. The author made key for analytical and interpretative treatments the poetics of panegyrics and canticles. Such a direction of analyzing literary works enables to prove that the presence of the genre, popular in past epochs, now, in the literature of the first half of the nineteenth century, is the result of searches for models of the perfect Polish character in “living history”, and the presented model rises to the symbol of patriotism, it becomes an example of action. By using the modernized form of the traditional panegyric concept, the image of the historical figure is authenticated and presented in the context of authentic, though appropriately selected facts. Therefore, the purpose of the article is an attempt to prove that the amplification of treatments are used in exhibiting the patriotic features of the heroine. First and foremost, they set the frames of the noble model of a woman and correspond with the new understanding of the category of heroism.